2016
DOI: 10.1007/s00107-016-1015-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design to determine the manufacturing parameters of a green-glued plywood panel

Abstract: The objective of this research was to investigate the technical feasibility of producing plywood by green-gluing technology. 2.5 mm thick rotary cut veneers obtained from steamed maritime pine (Pinus pinaster Ait.) logs were used. Plywood was manufactured under vacuum with veneers in a wet state. Five-layer plywood panels were produced using a one-component polyurethane adhesive to evaluate the effects of two parameters, the wood moisture content and the amount of adhesive, on the mechanical properties of plyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, on this substrate the adhesive mobility into the substrate porous is strongly influenced by wood moisture, owing to the side reaction occurring between NCO groups with water (free or bound) instead of with substrate reacting sites. Therefore, Bastani et al [234] thermally modified Scots wood pine to control its moisture content, while Lavalette et al [235] revealed the greater influence of moisture content on the ultimate shear strength than the amount of one-component polyurethane adhesive in the production of green-glued plywood. Hence, the considerable influence of water contact is apparent, although it can also be extended to curing and storage steps as shown by Chattopadhyay et al [236] or Asahara et al [217] when analyzing the curing kinetics under moisture conditions.…”
Section: Latest Advances In Bio-based Polyurethane Adhesivesmentioning
confidence: 99%
“…However, on this substrate the adhesive mobility into the substrate porous is strongly influenced by wood moisture, owing to the side reaction occurring between NCO groups with water (free or bound) instead of with substrate reacting sites. Therefore, Bastani et al [234] thermally modified Scots wood pine to control its moisture content, while Lavalette et al [235] revealed the greater influence of moisture content on the ultimate shear strength than the amount of one-component polyurethane adhesive in the production of green-glued plywood. Hence, the considerable influence of water contact is apparent, although it can also be extended to curing and storage steps as shown by Chattopadhyay et al [236] or Asahara et al [217] when analyzing the curing kinetics under moisture conditions.…”
Section: Latest Advances In Bio-based Polyurethane Adhesivesmentioning
confidence: 99%
“…However, a different specimen geometry was used because preliminary tests showed that the rupture occurred in the jaws of the standard specimen. More precisely, we used a "dumbbell" specimen [8], reinforced by wooden heels at the jaws, in order to ensure the rupture in the useful part of the sample. It was cut, respectively, in the parallel and perpendicular directions of the fibers in order to obtain the elasticity modulus in those two principal directions.…”
Section: Determination Of Elastic Properties Of the Bete Speciesmentioning
confidence: 99%
“…It was spread on the plies by using a notched squeegee so that the glue was evenly distributed. 3-ply plywood panels were manufactured by using the vacuum process technique [7,8]. The plies were oriented according to two arrangements options.…”
Section: Fabrication Of 3-ply Plywoodmentioning
confidence: 99%
See 1 more Smart Citation
“…When the vacuum is activated, a differential pressure is created between the inside and the outside of the bagging film that forces the plywood against the mould. Moreover, the glue migrates through the wood cells (Lavalette et al, 2016). Moulded plywood technology was initiated by the boating and aviation industries at the beginning of the 20th century.…”
Section: Vacuum Moulding Processmentioning
confidence: 99%